2016
DOI: 10.1186/s13075-016-1181-0
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses to de novo identified citrullinated fibrinogen peptides in rheumatoid arthritis and visualization of the corresponding B cells

Abstract: BackgroundAntibodies against citrullinated proteins (ACPA) are common in patients with rheumatoid arthritis (RA). ACPA can appear before disease onset and target many self-antigens. Citrullinated fibrin/fibrinogen represents a classical ACPA target antigen, and mass spectrometry of RA synovial fluid reveals elevated citrullinated (cit) fibrinogen (Fib) peptides compared to non-RA controls. We investigated the extent to which these less-studied peptides represent autoantibody targets and sought to visualize the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…They are found in different isotypes, including IgM, IgA and several subtypes of IgG, such as IgG1, IgG2, IgG3 and IgG4 [274]. ACPAs can be studied after purification from plasma or synovial fluid while autoreactive ACPA-producing B cells can be identified and visualized by the use of B cell tetramers [275][276][277]. These reagents allow ex vivo analysis of the cells and, by combining this method with sequencing technologies, even make it possible to examine their BCRs and transcriptional profiles.…”
Section: Citrulline-reactive B Cells and Autoantibodiesmentioning
confidence: 99%
“…They are found in different isotypes, including IgM, IgA and several subtypes of IgG, such as IgG1, IgG2, IgG3 and IgG4 [274]. ACPAs can be studied after purification from plasma or synovial fluid while autoreactive ACPA-producing B cells can be identified and visualized by the use of B cell tetramers [275][276][277]. These reagents allow ex vivo analysis of the cells and, by combining this method with sequencing technologies, even make it possible to examine their BCRs and transcriptional profiles.…”
Section: Citrulline-reactive B Cells and Autoantibodiesmentioning
confidence: 99%
“…[97][98][99] Fibrinogen is the soluble precursor of insoluble fibrin, the terminal component of the common coagulation pathway with thrombin responsible for the proteolysis of fibrinogen. 98,100 Thrombin, a trypsin-like serine protease, cleaves fibrinogen between Arg-16 and Gly-17 of the Aα chain and Arg-14 and Gly-14 of the Bβ chain to expose polymerization sites, resulting in release of fibrinopeptide A and fibrinopeptide from their respective N-terminal regions. 97,98 Fibrin monomers polymerize spontaneously, mediated by activated factor XIII (FXIIIa) that cross-link individual fibrin molecules to form a complex, stable, and insoluble branching network of fibrin fibers.…”
Section: Fibrinogen In Rheumatoid Arthritismentioning
confidence: 99%
“…Several studies observed no significant T-cell response or arthritogenic induction to citrullinated-fibrinogen immunization of HLA-DRβ1 transgenic mice. 100,102,103 However, the presence of antibodies to citrullinated fibrinogen (ACF) is associated with human HLA-DRβ1-0404 Ã allele along with early disease onset and radiographic progression. 104 The arthritogenic potential of citrullinated-fibrinogen in HLA-DR4 transgenic mice has also been reported by Raijmakers et al 55 Possible reasons for these discrepancies include increased ACPA heterogeneity in human RA, increased number of sites available for citrullination on human fibrinogen, and differences between the T-cell repertoire of humans and murine models.…”
Section: Fibrinogen In Rheumatoid Arthritismentioning
confidence: 99%
See 1 more Smart Citation
“…Although there may be few disagreements (Konig et al, 2016b ), the research data outlined above imply that citrullination, in conjunction with genetic factors, such as HLA-DRB1SE, protein tyrosine phosphatase nonreceptor type 22 (PTPN22) risk allele (Joshua et al, 2016 ) encoding an R620W amino acid change that allows survival of autoreactive B cells (Menard et al, 2011 ), is the key element in breaking tolerance. Thus citrullinated peptides may offer new therapeutic strategies for RA.…”
Section: Relevance To Treatmentmentioning
confidence: 99%